Educators, IT specialists and implicit descriptors for normality - Jana Marie Havigerová; Jiří Haviger (Czech Pedagogical Society, 2010)
The paper presents information on the results of research into implicit theo-ries of normality developed by teachers. This research was carried out within the projectof implicit theory of normality among helping professions (GA406/07/1397). The paper presents findings on implicit concepts of normality obtained from the analyses ofrepertory grid method and the focus group. We found and analysed both the structure and content of implicit theories developed by teachers and compared them with a group of IT specialists.